Basal, sham feed and pentagastrin stimulated gastric acid, pepsin and electrolytes after omeprazole 20 mg and 40 mg daily. Issue 10 (October 1985) - Thompson, J N; Barr, J A; Collier, N; Spencer, J; Bush, A; Cope, L; Gribble, R J; Baron, J H
Abstract : Gastric secretion was measured in nine patients with duodenal ulcer before, and after treatment for four weeks with omeprazole 20 mg or 40 mg daily. Basal acidity and acid output were affected variably by 20 mg, but inhibited totally by 40 mg daily. Sham feed stimulated acid output was reduced by 20 mg daily and completely inhibited by 40 mg daily. Maximal pentagastrin stimulated acid output was halved by 20 mg omeprazole daily and 84% inhibited by 40 mg daily. The reduction in acidity was always greater than the reduction of volume. Pepsin output after pentagastrin was little altered but with the reduced secretory volume pepsin concentrations were increased by both doses. The major cause of reduced aspirate acid output after omeprazole is decreased secretion of the primary acid component of the parietal cell by the proton pump H+K+ ATPase. Duodenogastric alkaline reflux is, however, markedly increased after omeprazole and is an additional factor in the resultant hypoacidity or even anacidity after this drug.